A New Upwind Finite Volume Element Method for Convection-Diffusion-Reaction Problems on Quadrilateral Meshes (Communications in Computational Physics, 2024)
This paper is devoted to constructing and analyzing a new upwind finitevolume element method for anisotropic convection-diffusion-reaction problems ongeneral quadrilateral meshes. We prove the coercivity, and establish the optimal error estimates in $H^1$ and $L^2$ norm respectively. The novelty is the discretization of convection term, which takes the two terms Taylor expansion. This scheme has not onlyoptimal first-order accuracy in $H^1$ norm, but also optimal second-order accuracy in $L^2$ norm, both for dominant diffusion and dominant convection. Numerical experimentsconfirm the theoretical results.